Eubacterium rectale Attenuates HSV-1 Induced Systemic Inflammation in Mice by Inhibiting CD83 - Islam, S. M. Shamsul; Ryu, Hye-Myung; Sayeed, Hasan M.; Byun, Hae-Ok; Jung, Ju-Yang; Kim, Hyoun-Ah; Suh, Chang-Hee; Sohn, Seonghyang (Frontiers in Immunology, 2021)
The purpose of this study was to determine whether administration of the microorganism Eubacterium rectale (E. rectale) could regulate dendritic cell (DC) activation and systemic inflammation in herpes simplex virus type 1-induced Behçet’s disease (BD). E. rectale, butyrate-producing bacteria, was administered to BD mice. Peripheral blood leukocytes (PBL) and lymph node cells were isolated and analyzed by flow cytometry. 16S rRNA metagenomic analysis was performed in the feces of mice to determine the differences in the composition of the microbial population between normal and BD mice. Serum cytokine levels were measured by enzyme-linked immunosorbent assay. The frequency of DC activation marker CD83 positive cells was significantly increased in PBL of BD mice. Frequencies of CD83+ cells were also significantly increased in patients with active BD. 16S rRNA metagenomic analysis revealed different gut microbiota compositions between normal and BD mice. The administration of E. rectale to BD mice reduced the frequency of CD83+ cells and significantly increased the frequency of NK1.1+ cells with the improvement of symptoms. The co-administration of colchicine and E. rectale also significantly reduced the frequency of CD83+ cells. Differences in gut microbiota were observed between normal mice and BD mice, and the administration of E. rectale downregulated the frequency of CD83, which was associated with BD deterioration. These data indicate that E. rectale could be a new therapeutic adjuvant for BD management.